FACTORS AFFECTING ACCESSIBILITY TO FINANCE BY SMALL AND MICRO ENTERPRISES IN ONGATA RONGAI - Mogeni, ONG’ERA; Geoffrey Mouni, DR GEKARA (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2015)
The Small and Medium Enterprises (SME’s) are important for raising the economic efficiency of a country. They are breeding grounds for entrepreneurship, innovations and inventions hence a reservoir for employment by creating sustainable jobs which in turn reduces the level of poverty. In Kenya, the SME’s have not grown to any notable impact often citing lack of finance. The Kenyan financial system is marked by a dualistic structure. It is characterized by the existence side by side of formal and informal financial markets. The informal suppliers of credit make up in part for the provision of the financial services. This then raises the issue on factors influencing accessibility to finance by SMEs in Kenya. The study looked at the size of an SME, collateral requirements; formalities involved in getting started, and SME sector as the study variable.This study adopted a descriptive research design where the population of interest were the SMEs. The target populations for this study were the employees of SMEs in Ongata Rongai in Kajiado County. The population was made up of 800 employees working in 308 registered SMEs in Ongata Rongai, where a sample size of 80 employees was selected for participation in the study. The process of data analysis involved several stages namely; data clean up and explanation. Data clean-up involved editing, coding, and tabulation in order to detect any anomalies in the responses and assign specific numerical values to the responses for further analysis. Completed questionnaires were edited for completeness and consistency. The data was coded and checked for any errors and omissions. Frequency tables, percentages and means were used to present the findings. Responses in the questionnaires were tabulated coded and processed by use of a computer Statistical Package for Social Science (SPSS) version 21.0 programme to analyze the data. The study revealed that older firms with reliable financial information were likely to access credit facilities than newly started firms. The study found that failure to have collateral had a negative effect on the SMEs access to financing in Ongata Rongai. The study revealed that lenders require extensive information like proper documentation of registration and/or an operating license, tax-compliance and externally audited financial statements. This study established that factors surrounding particular SMEs were key considerations when approving debts to SMEs.